M1 Stage Subdivision and Treatment Outcome of Patients With Bone‐Only Metastasis of Nasopharyngeal Carcinoma. (6th February 2015) - Shen, Lujun; Dong, Jun; Li, Sheng; Wang, Yue; Dong, Annan; Shu, Wanhong; Wu, Ming; Pan, Changchuan; Xia, Yunfei; Wu, Peihong
Abstract : Background: The current M1 stage in nasopharyngeal carcinoma (NPC) does not differentiate patients based on metastatic site and number of metastases. This study aims to subdivide the M1 stage of NPC patients with bone‐only metastases and to identify the patients who may benefit from combined chemoradiotherapy (CRT). Methods: Between 1998 and 2007, 312 patients diagnosed with bone‐only metastasis at Sun Yat‐sen University Cancer Center were enrolled. Various possible subdivisions of M1 stage were considered, including by the time order of metastasis (synchronous vs. metachronous), involvement of specific bone metastatic site, the number of metastatic sites, and the number of metastases. The correlation of the subdivisions of M1 stage with overall survival (OS) was determined by Cox regression. Results: The median OS was 23.4 months. Patients with more than three metastatic sites had significantly poorer OS than patients with three or fewer metastatic sites (16.2 vs. 32.4 months; p < .001). Metastasis to the spine was significantly associated with unfavorable OS (20.4 vs. 37.9 months; p < .001). Multivariate analysis showed that number of metastatic sites (more than three vs. three or fewer), spine involvement (present vs. absent), and treatment modality (CRT vs. chemotherapy or radiotherapy only) were independent prognostic factors for OS. In stratified analysis, compared with chemotherapy or radiotherapy alone, combined chemoradiotherapy could significantly benefit the patients with single bone metastasis (hazard ratio: 0.21; 95% confidence interval: 0.09–0.50). Conclusion: Metastasis to the spine and having more than three bone metastatic sites are independent unfavorable predictors for OS in NPC patients with bone‐only metastasis. Combined chemoradiotherapy should be considered for patients with single bone metastasis. Abstract : This study aimed to subdivide the M1 stage of patients with nasopharyngeal carcinoma (NPC) and bone‐only metastases and to identify the patients who may benefit from combined chemoradiotherapy (CRT). Metastasis to the spine and having more than three bone metastatic sites are independent unfavorable predictors for overall survival in patients with NPC and bone‐only metastasis. Combined CRT should be considered for patients with single bone metastasis. Abstract : 摘要 背景 。鼻咽癌 (NPC) 的现行 M1 期不基于转移部位和转移灶数目区分患者。这项研究旨在细分仅具有骨转移的 NPC 患者的 M1 期并鉴定可能从联合化放疗 (CRT) 中获益的患者。 方法 。1998 年至 2007 年在中山大学肿瘤防治中心招募了 312 位确诊仅具有骨转移的患者。考虑了 M1 期的多种可能细分，包括按照转移（同步与异时）的时间顺序、涉及的特定骨转移部位、转移部位数目和转移灶数目细分。通过 Cox 回归确定 M1 期细分与总生存期 (OS) 的相关性。 结果 。中位数 OS 是 23.4 个月。存在超过三个转移部位的患者比存在三个或更少转移部位的患者显著具有更差的 OS（16.2 个月对比 32.4 月；p < 0.001）。脊柱转移与不利 OS 显著相关（20.4 个月对比 37.9 月；p < 0.001）。多变量分析显示转移部位数目（超过三个对比三个或更少）、脊柱累及（存在对比不存在）和治疗模式（CRT 对比仅化疗或放疗）是 OS 的独立预后因素。在分层分析中，与单一化疗或放疗相比，联合化放疗可能显著有益于具有单一骨转移的患者（风险比：0.21；95% 置信区间：0.09–0.50）。 结论 。脊柱转移和具有超过三个骨转移部位是仅具有骨转移的 NPC 患者 OS 的独立不利预测因素。联合化放疗应当考虑用于具有单一骨转移的患者。 The Oncologist 2015; 20:291–298